Flagellar motility is required for the viability of the bloodstream trypanosome. - Broadhead, R; Dawe, H; Farr, H; Griffiths, S; Hart, SR; Portman, N; Shaw, M; Ginger, M; Gaskell, S; McKean, P; Gull, K (2006)
The 9 + 2 microtubule axoneme of flagella and cilia represents one of the most iconic structures built by eukaryotic cells and organisms. Both unity and diversity are present among cilia and flagella on the evolutionary as well as the developmental scale. Some cilia are motile, whereas others function as sensory organelles and can variously possess 9 + 2 and 9 + 0 axonemes and other associated structures. How such unity and diversity are reflected in molecular repertoires is unclear. The flagellated protozoan parasite Trypanosoma brucei is endemic in sub-Saharan Africa, causing devastating disease in humans and other animals. There is little hope of a vaccine for African sleeping sickness and a desperate need for modern drug therapies. Here we present a detailed proteomic analysis of the trypanosome flagellum. RNA interference (RNAi)-based interrogation of this proteome provides functional insights into human ciliary diseases and establishes that flagellar function is essential to the bloodstream-form trypanosome. We show that RNAi-mediated ablation of various proteins identified in the trypanosome flagellar proteome leads to a rapid and marked failure of cytokinesis in bloodstream-form (but not procyclic insect-form) trypanosomes, suggesting that impairment of flagellar function may provide a method of disease control. A postgenomic meta-analysis, comparing the evolutionarily ancient trypanosome with other eukaryotes including humans, identifies numerous trypanosome-specific flagellar proteins, suggesting new avenues for selective intervention.